THE EFFECTIVENESS OF USING ANIMATED VIDEO TO INCREASE THE STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT - Risa Sulfarida Arini; Gusti Nur Hafifah (Tell : Teaching of English Language and Literature Journal, 2017)
Writing skill is considered to be more complex and difficult to learn. Students’s skill in writing is still low. Thestudents get difficult to develop their ideas because based on the research, most of the students do not have anyvocabularies to write and they cannot develop the contents of the story. So, it is very important to help them inincreasing their ability in writing. The objective of this research is to find out wheter using animated video asmedium in writing narrative text is effective or not. This research is conducted at SMPN 1 Tarik Sidoarjo.Theresearcher used experimental design. The sample of this research was the eighth grade students with totalnumber was 68 students. The subject were VIII-C as the experimental class and VIII-D as the control classwhich each class consist of 34 students. It was gotten by random sampling. The data collection used test (try out,pre-test, and post test) as instrument to measure the the output of the students. From the data output that wasaccounted by using T-Test (α= 5%), the result of data analysis is tcount = 5.424 and ttable = 2.032, so tcount > ttable, itmeans that H0 is rejected and H1 is accepted. From this research, it can be concluded that there is significantdifference between the students who are taught by using animated video and those who are not taught by usinganimated video.